The wizard of Oz - Johnson,Richard; Lorraine Horsley; Lorraine Horsley; Catriona Macgregor (London Ladybird, 2013)
Dorothy, a young girl living in Kansas with her aunt and uncle, is caught in a tornado and transported to the magical Land of Oz. Her house lands on the Wicked Witch of the East, freeing the Munchkins and earning Dorothy the gratitude of the Good Witch of the North. Dorothy wants to return home, so she sets off on the Yellow Brick Road to find the Wizard of Oz, who is said to have the power to help her. Along the way, she meets three companions: the Scarecrow, who wants a brain; the Tin Man, who longs for a heart; and the Cowardly Lion, who seeks courage. Together, they face challenges and confront the Wicked Witch of the West. After melting the witch with water, they return to the Emerald City, only to discover the Wizard is an ordinary man with no magical powers. Despite this, he helps each of them see that they already possess what they were searching for. Eventually, Dorothy learns she can return home by clicking her heels together and saying, (3z(BThere$1 (Bs no place like home.(3y (BShe wakes up in Kansas, realizing it may have all been a dream$1 (Bbut she$1 (Bs learned the value of love, courage, and home.s
"The Wizard of Oz" is a beloved American fantasy story that follows Dorothy, a young girl from Kansas, who is swept away by a tornado to the magical land of Oz. As she journeys to find the Wizard who can help her return home, she meets memorable companions$1 (Bthe Scarecrow, Tin Man, and Cowardly Lion$1 (Beach seeking something they believe they lack. The story emphasizes themes of friendship, courage, self-discovery, and the idea that what we seek is often already within us.s
4-5 year old children.
Keywords: English Fiction book -- Fiction stories